Mashing-up wikis and forums: a case study of collaborative problem-based activity - Stylianou-Georgiou, Agni; Ioannou, Andri (My University, 2012)
A lot of studies have investigated the isolated use of threaded discussion and wiki technologies to facilitate collaboration in online learning settings. Nevertheless, the integration of both technologies into a potentially superior collaborative learning tool has not been explicitly investigated. This manuscript reports on an effort to undertake the merging and cooperation of wiki and threaded discussion technologies into a more sophisticated technology that better supports collaboration during problem-based activity in computer supported collaborative learning (CSCL) settings. Two customized collaboration technologies were investigated for their affordances to support students' cognitive processes and interactions during the construction of a group solution to an authentic problem. We found that one technology - WikiSplit - was particularly successful in promoting diversity of ideas (forum mode) while allowing learners to periodically update a group-owned document with syntheses of their emerging and shared understandings (wiki mode). We discuss how the integrated use of both a forum and a wiki, packaged together as one tool, can support and mediate desirable CSCL interactions during problem-based activity
Keywords: Wikis(Computer science); Online social networks--Computer programs